2006
DOI: 10.1089/lap.2006.16.63
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically Assisted Anorectal Pull-Through for High Imperforate Anus: Three Years' Experience

Abstract: Although longer follow-up to evaluate continence is to come, laparoscopically assisted anorectal pull-through should be considered for the correction of the high imperforate anus and, according to our experience, it represents the gold standard. It offers the advantage of good visualization of the fistula and the surrounding structures and minimally invasive abdominal and perineal wounds. With the laparoscopic Peña stimulator the direct observation of the contraction of the puborectalis sling allows an evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…Surgical stress was assessed using mean febrile period, duration of elevated white blood cell count, and peak C-reactive protein level. When CEQ were compared annually, scores for LAARP were generally higher throughout the study but only statistically significant at 3 and 4 years [2,3] 2 (11.8%) Kelly's score [6] 1 (6.9%) ▪ Proper position (75%) MRI [2,5,7,[11][12][13]16,17] 8 (47%) Ultrasound [2,3,17] 3 (17.6%) Barium enema [7,16] 2 (11.8%) ▪ Sphincter mechanism (29%) Manometry [4,6] 2 (11.8%) Digital examination [1,14,16] 3 (17.6%) ▪ Perineal appearance [9,13] 2 (11.8%) ▪ Urinary continence [13] 1 (6.9%) after surgery. The study concluded that although there were no significant differences between the 2 groups with regard to muscle thickness and parameters of surgical stress observed according to technique, LAARP appeared to provide better outcomes based on CEQ scores.…”
Section: Laarp Vs Psarpmentioning
confidence: 99%
“…Surgical stress was assessed using mean febrile period, duration of elevated white blood cell count, and peak C-reactive protein level. When CEQ were compared annually, scores for LAARP were generally higher throughout the study but only statistically significant at 3 and 4 years [2,3] 2 (11.8%) Kelly's score [6] 1 (6.9%) ▪ Proper position (75%) MRI [2,5,7,[11][12][13]16,17] 8 (47%) Ultrasound [2,3,17] 3 (17.6%) Barium enema [7,16] 2 (11.8%) ▪ Sphincter mechanism (29%) Manometry [4,6] 2 (11.8%) Digital examination [1,14,16] 3 (17.6%) ▪ Perineal appearance [9,13] 2 (11.8%) ▪ Urinary continence [13] 1 (6.9%) after surgery. The study concluded that although there were no significant differences between the 2 groups with regard to muscle thickness and parameters of surgical stress observed according to technique, LAARP appeared to provide better outcomes based on CEQ scores.…”
Section: Laarp Vs Psarpmentioning
confidence: 99%
“…Along with the improvement in operating techniques in neonatal surgery, a single-stage PSARP procedure has been developed for the treatment of imperforate anus [1][2][3]. In recent years, laparoscopic anorectoplasty [4][5][6], which involves a minimally invasive procedure, has become widespread, but considerable controversy remains with its application. In addition, the functional results after laparoscopic anorectoplasty are in need of long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Georgeson et al [5] and Lima et al [6] have popularized the laparoscopic approach to this aspect of the dissection. When the abdomen has been entered, it is relevant to consider a longitudinal reduction of the associated megarectum to reduce the longerterm "constipation" consequent on this excessive dilatation.…”
Section: Discussionmentioning
confidence: 99%